Pest Management Practices in the US Ornamental Horticulture Industry: Use of Neonicotinoid and Non-Neonicotinoid Insecticides - Hayk Khachatryan; Xuan Wei; Alicia Rihn (EDIS)
This article summarizes ornamental plant producers’ current production practices with a specific emphasis on their use of neonicotinoid and non-neonicotinoid insecticides. Written by Hayk Khachatryan, Xuan Wei, and Alicia Rihn, and published by the UF/IFAS Food and Resource Economics Department, July 2021.